2020
DOI: 10.3390/plants9121684
|View full text |Cite
|
Sign up to set email alerts
|

Sprout Regeneration of Shrub Willows after Cutting

Abstract: Shrub willow (Salix L. spp.) is a promising bioenergy resource crop due to its high growth rates and superb regenerative ability. Sprouting capacity is influenced by many factors, such as parent tree species and size, which are important limiting factors for stump survival or sprout growth. In this study, we aimed to quantify the survival and regeneration performance of sprouts (including sprout height, sprout diameter, sprout number, leaf morphological traits, leaf chlorophyll content, and ground part dry bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Almond-leaved willow research has been scarce, with generally little previously published data on the species [47][48][49][50]68]. Krüssmann [68] reported leaf length (LL) values in the range of 5 to 10 cm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Almond-leaved willow research has been scarce, with generally little previously published data on the species [47][48][49][50]68]. Krüssmann [68] reported leaf length (LL) values in the range of 5 to 10 cm.…”
Section: Discussionmentioning
confidence: 99%
“…Growing in a wide variety of habitats, on a wide range of soil types and in various altitudes, almond-leaved willow is empirically adaptable, although previous research to support the observed population variability is unknown to us. To this date, this species has been a part of a research into Salix germplasm [47] and some research into leaf anatomy [48,49] and sprout regeneration [50] has been conducted. Most recently, the pollen grain morphology has been analysed and the species has been separated from the other species within the subgenus Salix, but remained morphologically similar to numerous species from subgenera Chamaetria and Vetrix [51].…”
Section: Introductionmentioning
confidence: 99%